Penerapan Strategi Pemasaran dalam Meningkatkan Penjualan di Delastra Farm - Sari Listyani; Riyono Riyono (Lembaga Pengembangan Kinerja Dosen, 2025)
This Field Work Practice (KKL) was conducted at Delastra Farm Yogyakarta with the objective of analyzing the implementation of marketing strategies to increase sales in the livestock sector. The research employed a qualitative approach through observation, interviews with the business owner, and documentation review. Findings reveal that Delastra Farm adopts integrated marketing strategies combining online promotion, offline promotion, and community networking. The application of Segmentation, Targeting, and Positioning (STP) as well as the Marketing Mix (product, price, place, promotion) has significantly enhanced consumer trust and strengthened the farm’s market position. Peak sales were recorded during Eid al-Adha, supported by stock increases, intensive promotions, and delivery services that meet customer expectations. Supporting factors include product quality, the credibility of the owner as both practitioner and academic, and varied promotional strategies across digital and traditional platforms. However, the farm faces several challenges, such as limited capital, fluctuating feed prices, and intense competition within the livestock market. This study highlights the importance of digital marketing adoption, customer relationship management, and product diversification to reduce seasonal risks. The practical implication is that effective marketing strategies can improve not only sales performance but also long-term brand positioning for local livestock businesses. Theoretically, this activity demonstrates the relevance of applying marketing management concepts to micro and small-scale enterprises in the agricultural sector. Strategic recommendations include strengthening digital presence through social media and marketplaces, expanding partnerships with restaurants and religious institutions, and exploring external funding to support sustainable business growth.